Pelvic Floor Exercise for Post Partum Spontan Induction Rehabilitation, Indications of Chronic Energy Deficiency: A Case Report - Pramesti, Redita Salma Ayusandra; Rahayu, Umi Budi; Sulistyawati, Irma (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Post Partum Spontan Induction is a normal birthing process that refers to iatrogenic stimulation of uterine contractions before the start of spontaneous labor. The prevalence of induced labor increased significantly at the 41st week of pregnancy from 9.7% to 25.9%. The condition of pregnant women with the risk of chronic energy deficiency is at risk of decreasing muscle strength that helps the birth process, which can result in prolonged labor and postpartum bleeding. Case Presentation: This article was a case study of a patient at Rumah Sakit Khusus Ibu dan Anak Ummi Khasanah, Bantul, Yogyakarta (Mrs NA, 26 years old) after giving birth spontaneously induction due to chronic energy deficiency. The patient is given breathing exercises, active limb movement, transfer and ambulation exercises, pelvic floor exercises. Management and Outcome: Pelvic floor exercise is capable of strengthening the pelvic floor muscles and stimulating the recovery of the urogenital organs to their physiological function in post partum mothers. Discussion: The training provided is: pelvic floor exercise which aims to ensure that postpartum mothers can carry out functional activities well without any discomfort to the body parts that work during the birth process. Conclusion: Physiotherapy in the rehabilitation process for postpartum mothers is carried out 3 times over 2 days with administration pelvic floor exercise effective in reducing pain relief and increasing the patient's functional ability.